Orexin-A affects gastric distention sensitive neurons in the hippocampus and gastric motility and regulation by the perifornical area in rats. (September 2016) - Sun, Shu; Xu, Luo; Sun, Xiangrong; Guo, Feifei; Gong, Yanling; Gao, Shengli
Highlights: There is a direct pathway of orexin-A from the perifornical area to the hippocampus. The pathway is relevant to the regulation of gastric motility of rats. Electrical stimulation of the perifornical area promotes gastric motility. Orexin-A administration to the hippocampus is important in promoting gastric motility. Electrical stimulation and orexin-A regulate discharges of GD-responsive neurons. Abstract: Orexin-A is mainly produced in the lateral hypothalamus (LHA) and the perifornical area (PeF). Here, we aim to elucidate the effects of orexin-A in the hippocampus (Hi) on gastric distention (GD)-sensitive neurons and gastric motility, and potential regulation mechanisms by the PeF. Retrograde tracing and fluorescent-immunohistochemical staining were used to determine orexin-A neuronal projections. Single unit discharges in the Hi were recorded extracellularly and gastric motility in conscious rats was monitored during administration of orexin-A to the Hi or electrical stimulation of the PeF. Orexin-A administration to the Hi excited most of the GD-excitatory (GD-E) neurons and GD-inhibitory (GD-I) neurons, and increased gastric motility in a dose-dependent manner. All of effects induced by orexin-A could be partly blocked by pretreatment with orexin-A antagonist, SB-334867. Electrical stimulation of the PeF excited the majority of the orexin-A-responsive GD neurons in the Hi and promoted gastric motility. Additionally, pretreatment with SB-334867 in the Hi increased the firing rate of GDI and GDE neurons following electrical stimulation of the PeF. These findings suggest that orexin-A could regulate activities of GD-sensitive neurons and gastric motility. Furthermore, the PeF may be involved in this regulatory pathway.